Strengthening water governance and collective action through groundwater games - ElDidi, Hagar; Zhang, Wei; Gelaw, Fekadu; Obuobie, Emmanuel; Teka, Natneal; Akuriba, Margaret; Petris, Caterina de; Blackmore, Ivy; Yiman, Seid; Mekonnen, Dawit Kelemework; Ringler, Claudia; Meinzen-Dick, Ruth S. (2023)
As a result of growing food demands, more affordable drilling and pumping technologies, and climate change, groundwater resources are rapidly depleting in many places around the world.